KEDUDUKAN KLASULA BAKU DALAM PERJANJIAN BERDASARKAN UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Rahmat Noholo; Fence M Wantu; Dian Ekawaty Ismail (The Juris, 2023)
This article aims to find out how the position of the standard clause in an agreement in this case refers to consumer protection regulated in Law Number 8 of 1999 concerning Consumer Protection where the inclusion of standard clauses in an agreement both retail banking transactions and others as is still very much happening in everyday life, where when this clause is agreed upon by both parties then the agreement is considered binding and applies like a law for both of them However, on the other hand, there are opinions that oppose the inclusion of standard clauses in agreements, especially based on the principles of balance and fairness in contracting. By using descriptive analytical research methods and a normative juridical approach, the author wants to answer the extent of the validity and unenforceability of standard clauses in agreements and also how standard clauses in an agreement based on Law Number 8 of 1999 concerning Consumer Protection. The result of this research is that the prohibited standard clause is a clause in a standard agreement that contains a transfer of responsibility of the business actor. the transfer of responsibility has been regulated by the prohibition of its inclusion through Article 18 Paragraph (1) of the GCPL Law.